Macronutrient Content of Sipunculus nudus as an Antistunting Candidate - Warsidah (Jurnal Biologi Tropis, 2023)
Consuming balanced nutritious food with macronutrient content including carbohydrates, protein and fat for pregnant and breastfeeding mothers as well as children under five during the growth and development period is one of the efforts to prevent and treat anti-stunting, up to the age of 2 years. Waters and beaches are one of the habitats for marine biota such as bivalve shells, gastropods, various fish and other marine biota whose names and uses are not yet popular but are widely consumed by coastal communities, including Sipunculus nudus. Marine biota from the phylum Sipuncula in some areas are called sea worms, are one of the marine biota whose habitat is in the sand, and are the favorite food of coastal communities. Information about the nutritional and mineral content of this marine biota species has not been widely reported. This research aims to determine the macronutrient content of Sipunculus nudus collected from the coastal waters of Samboang, South Sulawesi. Determination of macronutrients was carried out using several methods, including for protein using the Kjeldahl method, fat using extraction with n-hexane solvent, water and ash content using an oven and furnace. The results of measuring the macronutrient content of Sipunculus nudus showed a water content of 72%, ash content of 1.19%, protein content of 6.5%, fat content of 2.07% and carbohydrate content using difference calculations was obtained at 18.24%.